Inflammation in Prostatic Hyperplasia and Carcinoma—Basic Scientific Approach - Krušlin, Božo; Tomas, Davor; Džombeta, Tihana; Milković-Periša, Marija; Ulamec, Monika (Frontiers in Oncology, 2017)
Chronic inflammation is associated with both benign conditions and cancer. Likewise, inflammatory cells are quite common in benign prostatic hyperplasia and prostatic tissue harboring cancer. Triggers which activate inflammatory pathways in the prostate remain a subject of argument and are likely to be multifactorial, some of these being bacterial antigens, different chemical irritations and metabolic disorders. Acute and chronic inflammation in prostate leads to accumulation of immunocompetent cells, mainly T lymphocytes and macrophages, but also neutrophils, eosinophils and mast cells, depending on the type of offending agent. Inflammatory processes activate hyperproliferative programs resulting in nodules seen in benign prostatic hyperplasia, but are also important in creating suitable microenvironment for cancer growth and progression. Inflammatory cells have mostly been shown to have a protumoral effect such as tumor associated macrophages, but some cell types such as mast cells, have antitumoral effects. This review outlines the recent findings and theories supporting the role of inflammatory responses as drivers of both benign and malignant epithelial processes in the prostate gland. Key words: inflammation, benign prostatic hyperplasia, prostatic carcinoma, inflammatory cells, cytokines